Nickel-based superalloy
By optimizing composition and heat treatment technology in nickel-based superalloys, the formation of a double-structure microstructure is solved, and the problem of insufficient creep resistance at high temperatures is achieved, and higher thermal mechanical properties and service life are achieved. and control alloy density and metallurgical stability.
Patent Information
- Application Number
- CN202380034033.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-17
- Filing Date
- 2023-03-14
- Publication Date
- 2024-12-27
AI Technical Summary
The existing nickel-based superalloys have shortcomings in their creep resistance and service life at high temperatures, especially at extreme temperatures around 850°C, which are difficult to meet the high requirements of the turbine disc.
Using a nickel-based superalloy with specific components, it contains elements such as aluminum, cobalt, chromium, molybdenum, tantalum, titanium, tungsten, boron, hafnium and zirconium. Through gradient heat treatment and tempering treatment, a double structure microstructure is formed to optimize grains. The method of size and carbide precipitation improves the thermomechanical properties of the alloy.
It significantly improves the creep resistance and service life of nickel-based superalloy at 850℃, extends the working life of the components, and controls the alloy density below 8.30g/cm3, ensuring the metallurgical stability and oxidation resistance of the alloy.
Smart Images

Figure BDA0005082913600000061 
Figure BDA0005082913600000111 
Figure BDA0005082913600000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of nickel-based superalloys for high temperature applications and developed for turbine disks with a coarse-grained / fine-grained dual structure. Improving the performance of engines and reducing their specific consumption requires increasing their operating temperatures. This means that new materials with greater heat resistance are needed. For turbine disks, the target temperature is about 800°C in nominal operation, with transient peaks of up to 850°C at the edges of the disk (i.e. close to the blades). In addition, the alloy must also have a strong resistance to traction and fatigue in the area close to the holes of the disk, because this area is subject to high stresses when the entire disk + turbine blade system rotates at a lower temperature (less than 700°C). These requirements can be achieved by combining two approaches: on the one hand, a process approach, which consists in developing the alloy by powder metallurgy and applying a dual structure heat treatment (patent FR3043410B1), which allows optimizing the grain size at the edges and in the holes of the disk; on the other hand, a material approach, which allows the chemical composition to be directly adapted to this method and significantly improves the mechanical properties. Background Art
[0002] The above requirements can be achieved by combining two approaches:
[0003] - On the one hand, the methodological approach consists in particular in developing the alloy by powder metallurgy and applying a heat treatment using a dual structure (patent FR3043410B1), making it possible to optimize the grain size both at the edge and in the hole of the disk;
[0004] - and on the other hand, the materials approach allows direct adaptation of the chemical composition to this approach and achieves a significant improvement in the mechanical properties.
[0005] Thus, a heat treatment method is known that makes it possible to obtain an alloy having such a dual structure, as described in patent application FR3043410. The present application proposes a method for producing a structural gradient on a disc-type component by a heat treatment that itself has a gradient. This is an induction heat treatment that allows solution treatment in the component with a staged temperature so that: - in the hotter zone, the temperature is above the dissolution temperature of the phase that blocks the grain boundaries, also called the solvus temperature (for gamma-gamma' nickel-based alloys; the phase in question is the gamma' phase);
[0006] - In the lower temperature region, the temperature is below the solvus temperature
[0007] Therefore, in the region where the heat treatment temperature exceeds the solvus temperature of the γ' phase, the grain size will increase to form a structure that is favorable for creep and cracking properties, while in the region where the heat treatment temperature remains below the solvus temperature, the structure will maintain the grain size produced by forging, which is generally relatively fine and favorable for tensile and fatigue properties.
[0008] Generally, the application of the gradient process is performed on an existing "conventional" alloy, whose chemical composition has been optimized to produce the best compromise in terms of the required mechanical properties, and a homogeneous structure throughout the component. Thus, the target operating temperature of the highest performing superalloys for disks is 760°C, with a peak of 800°C possible. However, the existing chemical composition is not optimal for the configuration of the gradient process. Therefore, it is necessary to define a chemical composition dedicated to the gradient process of the component to improve the performance of the component.
[0009] Safran Technologies and ONERA have jointly defined a nickel-based alloy composition that solves this problem for the first time (patent application FR3104613A1). The alloy is designed for turbine disk applications with a dual structure, where the grain size is optimized according to the mechanical characteristics required in each area of the component: the holes have a fine-grained microstructure to optimize their traction resistance and fatigue life, while the edges have a larger-grained microstructure to optimize their resistance to creep and crack growth. The coarse-grained microstructure is obtained by a local super-solution γ' (gamma') heat treatment. The alloy has a density of 8.24 g / cm 3 , compared with other known alloys (powder metallurgy alloy N19 is 8.34g / cm 3 ) is quite low and therefore very useful for this type of application. However, the supersolution γ' (gamma') heat treatment window for this composition is relatively narrow: there is only about 10 degrees difference between the alloy's solvus line γ' (gamma') and the solidus line. From an industrial point of view, this heat treatment is feasible, but the margin for error is small. In addition, even if the creep resistance of this alloy at 850°C is very useful, there are still means to optimize it to further extend the service life of components at such extreme temperatures.
[0010] Another nickel-based alloy composition is known from the prior art (application EP1840232) with a higher niobium content. However, their higher Nb content does not allow M 23 C6 carbides precipitate at 850°C and these carbides remain stable up to 900°C or even 920°C because Nb reduces the solvus temperature of these carbides to below 900°C, even below 800°C. However, this carbide improves the creep resistance of the alloy. Summary of the invention
[0011] The inventors have surprisingly found that such properties can be obtained using nickel-based superalloys which may contain tantalum, but in limited amounts and with a lower niobium content than the alloys described in FR3104613 and EP1840232, and in particular lower than the highest performing commercial alloy (N19 / SMO43).
[0012] Therefore, the present invention relates to a nickel-based superalloy, characterized in that, in terms of weight percentage of the total composition, its composition comprises, advantageously consists essentially of, in particular consists of:
[0013] Aluminum: 2.5–3.8, preferably 2.8–3.5;
[0014] Cobalt: 7.9–16.9, advantageously 8.2–16.6;
[0015] Chromium: 9.7–13.1, advantageously 10.0–12.8;
[0016] Molybdenum: 2.6–4.1, advantageously 2.6–3.8;
[0017] Nb: 0–0.41;
[0018] Tantalum: 0–1.9, advantageously 0–1.8;
[0019] Titanium: 4.4–6.4, advantageously 4.6–6.1;
[0020] Tungsten: 1.9–4.2, advantageously 2.2–4.0;
[0021] Boron: 0.010–0.030, advantageously 0.010–0.020;
[0022] Carbon: 0.010–0.040, advantageously 0.015–0.035;
[0023] Hafnium: 0.20–0.40, advantageously 0.20–0.35;
[0024] Zirconium: 0.040–0.070, advantageously 0.045–0.065;
[0025] The rest is nickel;
[0026] and inevitable impurities;
[0027] Wherein 12.5≤Al+Ti+Nb+Ta≤14%at., the contents of these elements are expressed in atomic percentage;
[0028] Wherein 0.85≤Al / (Ti+Nb+Ta)≤1.2, the contents of these elements are expressed in atomic percentage; and wherein Mo+W≥2.5%at., the contents of these elements are expressed in atomic percentage.
[0029] Therefore, the composition of the nickel-based superalloy according to the present invention contains the following elements:
[0030] -Main added elements: Co, Cr, Mo, W, Al, Ti, Ta;
[0031] - Minor added elements (lower concentrations expressed in mass %): Hf, C, B, Zr, Nb.
[0032] Thus, the composition according to the invention comprises aluminum (Al) in an amount ranging from 2.5 to 3.8, advantageously 2.8 to 3.5, in particular 2.82 to 3.43, more particularly 2.9 to 3.3, expressed in weight percentage relative to the total weight of the composition. The measurement uncertainty of the aluminum content is ±0.10.
[0033] The composition according to the invention also comprises cobalt (Co) in an amount ranging from 7.9 to 16.9, advantageously 8.2 to 16.6, in particular 8.2 to 15.6, more particularly 12.0 to 14.0, expressed in weight percentage relative to the total weight of the composition. The measurement uncertainty of the cobalt content is ±0.4.
[0034] The composition according to the invention also comprises chromium (Cr), in a weight percentage range of 9.7-13.1, advantageously 10.0-12.8, in particular 10.8-12.8, more particularly 10.9-12.7, even more particularly 11.65-12.7, relative to the total weight of the composition. The measurement uncertainty of the chromium content is ±0.35.
[0035] The composition according to the invention also comprises molybdenum (Mo) in an amount ranging from 2.6 to 4.1, advantageously 2.6 to 3.8, in particular 2.7 to 3.25, in weight percent relative to the total weight of the composition. The measurement uncertainty of the molybdenum content is ±0.11.
[0036] The composition according to the invention also comprises niobium (Nb) in an amount ranging from 0 to 0.41% by weight relative to the total weight of the composition. In an advantageous embodiment, the composition is free of niobium. In another advantageous embodiment, the content of niobium in the composition is at most 0.41% by weight relative to the total weight of the composition, in particular in the range of 0.39-0.41%, more particularly in the range of 0.40-0.41%. The measurement uncertainty of the niobium content is ±0.10.
[0037] The composition according to the invention also comprises tantalum (Ta), in a weight percentage range of 0–1.9, advantageously 0–1.8, relative to the total weight of the composition. In an advantageous embodiment, the composition is tantalum-free. In fact, tantalum (Ta) contributes to strengthening the γ' phase, but has the effect of increasing the density of the alloy. In another advantageous embodiment, the composition contains tantalum in a weight percentage of at most 1.9%, in particular at most 1.6%, more particularly in the range of 1-1.6%, relative to the total weight of the composition. The measurement uncertainty of the tantalum content is ±0.15.
[0038] The composition according to the invention also comprises titanium (Ti), the content of which ranges from 4.4 to 6.4, advantageously from 4.6 to 6.1, in percentage by weight relative to the total weight of the composition. The uncertainty of the measurement of the titanium content is ±0.15.
[0039] The composition according to the invention also comprises tungsten (W), the content of which ranges from 1.9 to 4.2, advantageously from 2.2 to 4.0, in weight percentage relative to the total weight of the composition. The measurement uncertainty of the tungsten content is ±0.16.
[0040] The composition according to the present invention further comprises boron (B), the content of which, in weight percentage, relative to the total weight of the composition, ranges from 0.010 to 0.030, in particular from 0.010 to 0.020. The measurement uncertainty of the boron content is ±0.003.
[0041] The component according to the invention also comprises carbon (C) in an amount ranging from 0.010 to 0.040, advantageously from 0.015 to 0.035, in particular from 0.020 to 0.035, expressed as a percentage by weight relative to the total weight of the component. The measurement uncertainty of the carbon content is ±0.003.
[0042] The composition according to the invention also comprises hafnium (Hf), the content of which ranges from 0.20 to 0.40, advantageously from 0.20 to 0.35, in percentage by weight relative to the total weight of the composition. The measurement uncertainty of the hafnium content is ±0.002.
[0043] The composition according to the invention also comprises zirconium (Zr) in an amount ranging from 0.040 to 0.070, advantageously from 0.045 to 0.065, in particular from 0.055 to 0.060, expressed as a percentage by weight relative to the total weight of the composition. The measurement uncertainty of the zirconium content is ±0.003.
[0044] The nickel-based alloy according to the present invention contains the elements cobalt, aluminum, titanium, niobium and tantalum for forming an ordered structure L12 and hardening γ' (gamma') precipitates of the composition (Ni,Co)3(Al,Ti,Nb,Ta). However, the tantalum content is limited to avoid excessively increasing the density of the alloy, the target being less than or equal to 8.30 g / cm 3 .
[0045] The niobium content is limited to 0.41% (by weight) because this element stabilizes MC carbides (where M = Ti, Nb) at the expense of M 23 C6 carbide (where M = Cr, Mo or W). Excessive niobium content will lead to M 23 The solvus temperature of C6 carbide is reduced to below 900°C. 23 The minimum solvus value of C6 carbide is advantageously fixed at 900°C (solvus M 23 C6≥900℃), preferably fixed at 920℃ (solvus line M 23 C6≥920℃) to ensure its stability at 850℃ and to maintain a certain margin when the temperature peak of the disk increases in future operation.
[0046] Carbon, boron, zirconium and hafnium enhance the high temperature resistance of grain boundaries. Carbon can also form carbides M 23 C6 (wherein M = Cr, Mo or W).
[0047] Molybdenum and tungsten contribute to the thermomechanical strengthening of the alloy. Their content is optimized to maximize this strengthening while limiting the precipitation of σ or μ TCP (topologically dense) phases, which reduce mechanical strength. These elements also participate in the formation of carbides M 23 The formation of C6 (where M = Cr, Mo or W). In particular, the presence of W participates in the formation of carbides M 23 Formation and stabilization of C6. The sum of their contents expressed in atomic percentages must comply with the rule Mo+W ≥ 2.5% at. (the contents of these elements are expressed in atomic percentages), in particular in order to ensure a minimum strengthening by solid solution in the γ (gamma) matrix.
[0048] Chromium is present because it participates in the carbide M 23 The formation of C6 (where M=Cr, Mo or W) allows to improve the oxidation resistance of the alloy by forming a continuous passive layer on the surface. However, the chromium content is limited in order to avoid promoting the precipitation of the TCP phase to which it belongs.
[0049] The heat-resistant mechanical properties of the alloy are determined by the molar fraction of γ'(gamma') precipitates, which is between 50% and 56%. The elements Al, Ti, Nb and Ta (expressed in atomic percentage) meet the criterion 12.5≤Al+Ti+Nb+Ta≤14%at. In order to favor the precipitation of the γ'(gamma) phase compared to the η-Ni3Ti phase, which is not ideal from the perspective of mechanical properties, the elements Al, Ti, Nb and Ta meet the criterion 0.85≤Al / (Ti+Nb+Ta)≤1.2, and the contents of these elements are expressed in atomic percentage. These criteria mean that it is necessary to optimize the content of titanium, niobium and tantalum in the γ'(gamma) phase to maximize the thermomechanical strengthening properties of the alloy while avoiding promoting the formation of the η phase to the detriment of γ'(gamma).
[0050] The unavoidable impurities in the composition according to the invention come from the steps of manufacturing the superalloy or from impurities present in the raw materials used to manufacture the superalloy. All common impurities encountered are present in nickel-based superalloys. In particular, they are selected from the group consisting of manganese, silicon, vanadium, sulfur, phosphorus, copper, lead, iron, bismuth, nitrogen, oxygen, hydrogen and mixtures thereof. They account for a maximum of 1% of the weight of the alloy, each impurity not exceeding 0.5% of the weight of the total composition. Typically, the uncertainty of measurement of the impurity content in the alloy is 10%.
[0051] In an advantageous embodiment, the nickel-based superalloy according to the invention is characterized in that, in terms of weight percentage of the total composition, its composition comprises, advantageously consists essentially of, in particular consists of:
[0052] Aluminum: 2.8-3.5;
[0053] Cobalt: 8.2–15.6;
[0054] Chromium: 10.8-12.8;
[0055] Molybdenum: 2.7-3.25;
[0056] Nb: 0–0.41;
[0057] Tantalum: 0–1.9;
[0058] Titanium: 4.6–6.1;
[0059] Tungsten: 2.2–4.0;
[0060] Boron: 0.010-0.030, advantageously 0.010-0.020;
[0061] Carbon: 0.010-0.040, advantageously 0.015-0.035;
[0062] Hafnium: 0.20-0.40, advantageously 0.20-0.35;
[0063] Zirconium: 0.040-0.070, advantageously 0.045-0.065;
[0064] The rest is nickel and unavoidable impurities;
[0065] Wherein 12.5≤Al+Ti+Nb+Ta≤14%at., the contents of these elements are expressed in atomic percentage;
[0066] Where 0.85≤Al / (Ti+Nb+Ta)≤1.2, the contents of these elements are expressed in atomic percentage;
[0067] Among them, Mo+W≥2.5%at., and the contents of these elements are expressed in atomic percentage.
[0068] Specifically, the composition of the superalloy according to the present invention may be as shown in Table 1 below.
[0069] [Table 1]
[0070]
[0071] M in grain boundary 23 The thermal creep resistance is enhanced by the precipitation of C6 carbides, where M = Cr, Mo or W. These carbides are discretely precipitated during a tempering operation at a temperature of less than or equal to 870°C (preferably less than or equal to 850°C) for 2 hours to 16 hours and have a size of less than 5 μm, preferably less than 1 μm. The carbide M calculated using the CALPHAD (phase diagram calculation) method is 23 The amount of C6 (M = Cr, Mo or W) is advantageously between 0.4% and 1% mol at 850°C (0.4% at 850°C). <M 23 C6 <1 mol %), preferably between 0.5% and 0.8 mol % at 850°C (0.5% at 850°C <M 23 C6 <0.8 mol%) to obtain a sufficient carbide population to ensure the required hardening while avoiding grain boundary saturation, which would promote undesirable intragranular precipitation and weaken the alloy. 23 The solvus temperature of C6 (where M=Cr, Mo or W) is advantageously greater than 900°C to avoid carbide redissolution in case of temperature peaks above 850°C in operation, and preferably greater than 920°C to compensate for possible future temperature increases during these peaks.
[0072] In an advantageous embodiment, the density of the superalloy according to the invention is less than 8.50 g / cm 3 , advantageously less than 8.30 g / cm 3. The room temperature density of each superalloy was estimated using a modified version of the Hull equation. . The empirical equation was proposed by Hull (FC Hull, Metal Progress, November 1969, pp. 139-140). The empirical equation is based on the law of mixtures and includes correction terms derived from linear regression analysis of experimental data (chemical composition and measured density) on 235 superalloys and stainless steels. The Hull formula was modified based on data related to 272 nickel-based, cobalt-based, and iron-based superalloys. The modified Hull formula is as follows:
[0073] [Mathematical formula 1]
[0074] D·=·100· / ·[∑·(%X / DX)]·+·∑·AX·x·%X
[0075] Where DX is the density of the X element (Cr, Ni, etc.), D is the density of the superalloy, and the density unit is g / cm 3 , where AX is the coefficient of the X element (Cr, Ni, etc.), in g / cm 3 , respectively: ANi=-0.0011; AAl=0.0622; ATa=0.0121; ATi=0.0317; ANb=0.011; ACo=-0.0001; ; ACr=-0..0034; AMo=0.0033; AW=0.0033; AHf=0.0156; and wherein %X is the content of X element (Cr, Ni, etc.) in the superalloy expressed as a percentage by mass.
[0076] In another advantageous embodiment, the superalloy according to the present invention has metallurgical stability up to 800° C.-850° C. (ie, no TCP phase—topologically dense phase—is present).
[0077] In another advantageous embodiment, the superalloy according to the invention has good oxidation resistance.
[0078] In yet another advantageous embodiment, the difference between the solidus temperature γ (gamma) and the solvus temperature γ' (gamma') of the superalloy according to the invention is large enough to allow heat treatment, advantageously the difference is at least 20°C ([solidus γ-solvus γ'] ≥ 20°C).
[0079] In an advantageous embodiment, the nickel-based superalloy according to the invention is free of tantalum and / or niobium, advantageously free of tantalum and niobium.
[0080] In a further advantageous embodiment, the nickel-based superalloy according to the invention contains tantalum and / or niobium.
[0081] The invention also relates to a superalloy powder according to the invention. In fact, the superalloy according to the invention may be in the form of a powder with a particle size between 10 μm and 100 μm.
[0082] The present invention also relates to a method for producing a nickel-based superalloy powder according to the present invention, the method comprising the following steps:
[0083] A – Mixing elemental raw materials or pre-alloyed raw materials;
[0084] B - melting the mixture obtained in step A), advantageously in a vacuum induction furnace (VIM);
[0085] C—gas atomization (advantageously with argon) of the product obtained in step B) so as to obtain a powder which is advantageously predominantly spherical (in other words, without sharp corners);
[0086] D— sieving the powder obtained in step C) under advantageously an inert atmosphere to obtain the target particle size;
[0087] E – Recover the obtained powder.
[0088] The method may further include the following consecutive steps after step E:
[0089] F – Filling the powder into a container (especially a cylindrical container, more specifically under vacuum);
[0090] G – hot pressing of the filled container, for example by hot uniaxial pressing (HUP) in a press, or by hot isostatic pressing (HIP), in particular in an autoclave;
[0091] H – hot spinning powder container (the container passes through a die that reduces its diameter. This allows obtaining cylindrical rods with a 100% dense, fine and uniform structure),
[0092] I – stripping (to remove the peripheral sheath corresponding to the initial container wall) and control operations, in particular by ultrasound;
[0093] J – Cut into segments.
[0094] The particle size of the powder is therefore adjusted to the manufacturing technology of the component based on the superalloy powder under consideration. The particle size range used for different manufacturing methods varies depending on the technology, equipment and target application. In general, the powders used for these methods will have a more or less broad particle size distribution between 10 μm and 100 μm if all applications are combined.
[0095] The invention also relates to a method for producing a component, in particular a turbine, made of a superalloy according to the invention or a superalloy powder according to the invention, characterised in that the method comprises the following steps:
[0096] a – forging,
[0097] b – gradient heat treatment of the component obtained in step a),
[0098] c – final heat treatment of the entire component with the duplex microstructure obtained in step b),
[0099] d - Recycling of the components obtained in step c).
[0100] The forging step a) can be carried out by methods well known to those skilled in the art, in particular for the segment obtained in step J. For example, it can be stamping (for example isothermal forging). This technique is well known to those skilled in the art. This step a) allows obtaining a superalloy component.
[0101] The gradient heat treatment step b) can be implemented using the method and apparatus described in patent application FR3043410.
[0102] Advantageously, step b) of subjecting the component obtained in step a) to gradient heat treatment comprises:
[0103] b1 - a region of a component is first heated to a first temperature (T1) that is above the solvus temperature of the γ' phase of the superalloy and below the melting temperature of the superalloy.
[0104] Thus, it may consist in heating a region of the component (e.g. the edge of a disk) to a first temperature (T1) which is at least 5°C higher than the solvus temperature of the γ' phase of the superalloy (advantageously between +5°C and +15°C relative to the solvus temperature of the γ' phase of the superalloy) and lower than the melting temperature of the superalloy (this is therefore a supersolution treatment, that is to say a supersolution dissolution). The duration of this treatment may be between 1 hour and 8 hours.
[0105] The gradient heat treatment may be performed, for example, by localized induction heating or by any of the methods or devices described in FR3043410.
[0106] If the component is a turbine disk, the area of the component subjected to the first temperature (T1) consists of the edge area of the disk, the remainder being unaffected by the treatment.
[0107] Thus, the supersolution treatment (temperature T1) allows to use 100% of the hardening potential associated with the gamma 'phase to maintain effective hardening still at high temperatures (800 ° C, even able to withstand peaks of 850 ° C), while increasing the resistance of the alloy to thermal creep and crack growth by increasing the grain size. Thus, advantageously, the grain size is greater than or equal to 15 μm (measured by the intercept method). The grain size is advantageously 40 μm on average to maintain good fatigue resistance.
[0108] Thus, step b) allows to obtain a component with a dual or gradient microstructure, that is to say, without a homogeneous microstructure, and in particular with grain sizes that are not the same, depending on whether a super solution treated area of the component or an area not affected by the super solution treatment is considered. Thus, the area of the component that has been super solution treated comprises coarse grains, while the area not affected by the super solution treatment comprises fine grains. Thus, the component with a dual or gradient microstructure according to the invention comprises coarse grains and fine grains, advantageously the size of the coarse grains being greater than or equal to 15 μm, in particular in the areas of the component that have been super solution treated, such as in the edges of the disk, and the size of the fine grains, in particular fine grains from forging, being less than 15 μm, in particular in the areas of the component that have not been affected by the super solution treatment, such as in the holes of the disk. The grain size is measured by the intercept method.
[0109] Step c) of the method of the present invention may comprise the following consecutive steps:
[0110] c1 - placing the entire component obtained in step b) in a solution having a temperature lower than the solvus temperature (T2) of the γ' phase of said superalloy (it is therefore a sub-solution treatment or a sub-solution solution), for example a temperature T2 comprised between -80°C and -20°C relative to the solvus of the γ' phase;
[0111] c2—The entire component obtained in step c1) is cooled or quenched; advantageously, the cooling rate is adjusted according to the mass of the component to obtain the best size and distribution of the γ' hardened phase, more advantageously, the cooling rate is about 100°C / min (the rate can vary between 80°C / min and 120°C / min depending on the location).
[0112] c3—subjecting at least one tempering treatment to part or all of the component obtained in step c2), advantageously at a temperature in the range of 730° C. to 870° C., in order to precipitate M 23 C6 type carbides (where M=Cr, Mo or W).
[0113] The final heat treatment of step c) is therefore a conventional heat treatment of γ / γ' alloys. The purpose of this treatment is to treat the structure not affected by the gradient treatment in order to have a final structure in these zones so that the mechanical properties reach the desired level. In fact, in the areas treated only with a subsolution (temperature T2), the grain size remains low, advantageously less than 10 μm (measured by the intercept method), making it possible to obtain good tensile and fatigue properties at average temperatures (for example below 750°C). Therefore, this second solution allows to refine the size of the γ' (gamma') precipitates throughout the part while maintaining a fine grain size in the areas that have not undergone the first solution. The part thus obtained has a grain size of 6-7 ASTM (28-40 μm) in the edges that will be subjected to creep at very high temperatures, and a grain size of 10-12 ASTM (5-10 μm) in the rest of the part that is mainly subjected to traction and fatigue stresses at lower temperatures.
[0114] The duration of step c1) may be between 1 hour and 8 hours.
[0115] In particular, step c3) may consist of one or more tempering treatments, advantageously two tempering treatments. This may be a single or double tempering treatment.
[0116] Therefore, a relatively hot final tempering treatment (for example a first tempering in the range of 730°C-870°C, in particular 730°C-850°C, for example at a temperature of about 850°C, more particularly at 850°C, followed by a second tempering at a temperature between 730°C and 800°C, advantageously around 800°C, in particular at 800°C) allows stabilization of the microstructure of the component at high temperature and also allows the release of residual stresses caused by the quenching associated with the treatment at temperature T2.
[0117] The duration of step c3) may be 2 hours to 24 hours (for example a first tempering duration of 4 hours to 8 hours, in particular at a temperature of 850° C., followed by a second tempering duration of 4 hours to 16 hours, in particular at a temperature of 800° C.).
[0118] The tempering and quenching treatments are carried out using techniques known to those skilled in the art.
[0119] The purpose of tempering heat treatment is to precipitate M 23 C6 type carbides (where M = Cr, Mo or W) and stabilize the γ' (gamma') precipitate group. Therefore, the first tempering treatment is performed to precipitate spherical carbides M 23 C6 (where M = Cr, Mo or W) followed by a second tempering treatment to stabilize the γ' (gamma') precipitate population at a temperature close to the target operating temperature of the hottest part of the disk.
[0120] These thermal tempering treatments can be carried out uniformly over the entire component, but it is also possible to treat only a portion of the component in order to optimize the tempering according to the target properties of each area. For example, only the supersolution treated area of the component (e.g. the edge of the disk) is tempered at a temperature of about 850°C (advantageously 850°C) to precipitate the carbides M 23 C6, then treat the entire part at a temperature between 730°C and 800°C to stabilize the precipitates γ' (gamma') in the pores of the part. This allows the precipitation of M by precipitating at 850°C 23 C6 carbides are added to optimize the creep resistance of the edges, but do not lead to an increase in γ' precipitation in the pores of the disk, thereby retaining the finest γ' precipitation to optimize the tensile strength in this area.
[0121] The invention finally relates to a component made of a superalloy according to the invention or a superalloy powder according to the invention, the component having a dual microstructure, advantageously obtainable by a method according to the invention. Advantageously, the component is a turbomachine component, more advantageously a turbine component, in particular a turbine disk, a compressor disk, a ring, a flange or a turbine housing, more particularly a turbine disk, for example a turbine disk of an aircraft and / or helicopter engine.
[0122] The component according to the invention thus has a dual microstructure or a gradient microstructure, that is to say it does not have a homogeneous microstructure. In particular, the grain size of the component varies from region to region of the component. It thus comprises coarse grains and fine grains, advantageously the coarse grain size being greater than or equal to 15 μm, advantageously 40 μm on average, and the fine grain size being less than 15 μm. Thus, advantageously one region of the component comprises coarse grains, while the remainder of the component and / or another region of the component comprises fine grains. Thus, if the component is a turbine disk, the edge region of the disk has coarse grains, advantageously with a grain size greater than or equal to 15 μm, advantageously 40 μm on average, while the hole region of the disk has fine grains, advantageously with a grain size less than 15 μm. The grain size is measured by the intercept method.
[0123] Advantageously, the coarse-grained area of the piece has good creep resistance at a temperature of 850°C according to standard NF EN ISO 204 (August 2009), more advantageously the duration to reach 0.2% elongation at a stress of 200 MPa and a temperature of 850°C is greater than 37 hours.
[0124] Advantageously, the fine-grained region of the component has good tensile strength at temperatures below 750° C., in particular an elastic limit of greater than 1100 MPa at 20° C., according to standard NF EN 2002-001 / 06.
[0125] The present invention will be better understood with reference to the accompanying drawings and the following description of examples, which are provided for reference only and are not intended to be limiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0126] Figure 1 An image of a forged disk with a gradient microstructure is shown, with coarse grains of 28 μm-40 μm at the edge and fine grains of 5 μm-10 μm in the rest of the component. The transition region between the two microstructures is schematically shown with a dashed line. DETAILED DESCRIPTION
[0127] The nickel-based superalloys according to the present invention (Examples 1 to 8 and Examples 10 to 17) were manufactured by vacuum casting an ingot, atomizing the ingot under argon, sieving to 53 μm, placing the powder in a container and degassing, and then hot spinning the powder into a rod shape. The nickel-based superalloy of Example 9 was produced by VIM casting according to a method known to those skilled in the art. They were compared with 5 superalloys: 1 superalloy according to the example of application FR3104613 (Example FR3104613A1), 1 superalloy according to the example of application EP1840232 (Example EP1840232), and 3 superalloys with too high niobium content (Comparative Examples 18 to Comparative Examples 20)
[0128] The alloys produced according to the present invention have the chemical compositions in weight % shown in Table 1 above. The five comparative superalloys have the compositions shown in Table 2 below.
[0129] [Table 2]
[0130]
[0131]
[0132] The calculated solvus γ' (gamma) and solidus temperatures and the solidus-solvus γ' (gamma) differences for the different alloys are shown in Table 3 below. Table 3 also shows the density estimated using the modified Hull formula above. Table 3 also shows the values of the formula Al+Ti+Nb+Ta (in % at.) and Al / (Ti+Nb+Ta) (in % at.).
[0133] A portion of the bar is then treated at 1180°C to 1200°C for 2 hours (super solution treatment) and then cooled at a rate of about 30°C / min. The entire bar is then treated at 1145°C to 1165°C for 2 hours (sub-solution treatment), followed by quenching at 100°C / min and tempering at 850°C for 4 hours to 8 hours, followed by a second tempering at 800°C for 4 hours to 16 hours. M calculated using the CALPHAD (phase diagram calculation) method 23 The amount of C6 carbide is shown in Table 3. 23 The solvus temperature of C6 carbide is also shown in Table 3.
[0134] [Table 3]
[0135]
[0136]
[0137] Compared with current solutions (FR3104613 alloy or EP1840232 alloy in this case), the advantages obtained by the present invention are twofold: the first advantage is that it is easier to implement industrially due to the expansion of the heat treatment window for grain coarsening from 10°C to 20°C or higher, while the second advantage is the extension of the service life of the components at extremely high temperatures (850°C).
[0138] The alloy according to the invention has better creep resistance at 850°C, which results in a longer service life of the component in terms of creep. At this temperature, the grain boundaries are considered to be weak points in the microstructure. This is why grain size enlargement is used to reduce the density of grain boundaries and thus limit their influence. In the new alloy, this coarsening is also associated with the increase of M in the grain boundaries. 23 The quenching of the creep is related to the precipitation of C6 carbides. These carbides are intended to strengthen the grain boundaries to limit the creep diffusion mechanism and slow down the metal deformation caused by creep, thus allowing the component to operate at 850°C for longer periods of time.
Claims
1. A nickel-based superalloy, characterized in that: The composition of the nickel-based superalloy includes, advantageously consists essentially of, the following in terms of weight percentage of the total composition: Aluminum: 2.5–3.8, preferably 2.8–3.5; Cobalt: 7.9–16.9, advantageously 8.2–16.6; Chromium: 9.7–13.1, advantageously 10.0–12.8; Molybdenum: 2.6–4.1, advantageously 2.6–3.8; Nb: 0–0.41; Tantalum: 0–1.9, advantageously 0–1.8; Titanium: 4.4–6.4, advantageously 4.6–6.1; Tungsten: 1.9–4.2, advantageously 2.2–4.0; Boron: 0.010–0.030, advantageously 0.010–0.020; Carbon: 0.010–0.040, advantageously 0.015–0.035; Hafnium: 0.20–0.40, advantageously 0.20–0.35; Zirconium: 0.040–0.070, advantageously 0.045–0.065; The rest is nickel and inevitable impurities; Wherein 12.5≤Al+Ti+Nb+Ta≤14%at., the contents of these elements are expressed in atomic percentage; Wherein 0.85≤Al / (Ti+Nb+Ta)≤1.2, and the contents of these elements are expressed in atomic percentages; and Among them, Mo+W≥2.5%at., and the contents of these elements are expressed in atomic percentage.
2. The nickel-based superalloy according to claim 1, characterized in that The composition includes, advantageously mainly consists of, in terms of weight percentage of the total composition: Aluminum: 2.8–3.5; Cobalt: 8.2–15.6; Chromium: 10.8–12.8; Molybdenum: 2.7–3.25; Nb: 0–0.41; Tantalum: 0–1.9; Titanium: 4.6–6.1; Tungsten: 2.2–4.0; Boron: 0.010–0.030, advantageously 0.010–0.020; Carbon: 0.010–0.040, advantageously 0.015–0.035; Hafnium: 0.20–0.40, advantageously 0.20–0.35; Zirconium: 0.040–0.070, advantageously 0.045–0.065; The rest is nickel and inevitable impurities; Wherein 12.5≤Al+Ti+Nb+Ta≤14%at., the contents of these elements are expressed in atomic percentage; Where 0.85≤Al / (Ti+Nb+Ta)≤1.2, the contents of these elements are expressed in atomic percentage; Among them, Mo+W≥2.5%at., and the contents of these elements are expressed in atomic percentage.
3. The nickel-based superalloy according to any one of claims 1 or 2, characterized in that Temperature difference [solidus γ-solvus γ'] ≥ 20℃.
4. The nickel-based superalloy according to any one of claims 1 to 3, characterized in that M 23 C6 carbide content at 850°C is 0.4% <M 23 C6 <1 mol%, where M = Cr, Mo or W, advantageously 0.5% at 850°C <M 23 C6<0.8 mol%, where M=Cr, Mo or W.
5. The nickel-based superalloy according to any one of claims 1 to 4, characterized in that The carbide M 23 The solvus temperature of C6 is ≥900°C, wherein M=Cr, Mo or W. Advantageously, the carbide M 23 The solvus temperature of C6 is ≥920°C, where M=Cr, Mo or W.
6. The nickel-based superalloy according to any one of claims 1 to 5, characterized in that The nickel-based superalloy does not contain tantalum and / or niobium.
7. The nickel-based superalloy according to any one of claims 1 to 5, characterized in that The nickel-based superalloy contains tantalum and / or niobium.
8. The superalloy powder according to any one of claims 1 to 7.
9. A method for producing a superalloy component according to any one of claims 1 to 7 or a superalloy powder according to claim 8, characterized in that: The method comprises the following steps: a – forging, b – gradient heat treatment of the component obtained in step a), c – final heat treatment of the entire component with the duplex microstructure obtained in step b), d - Recycling of the components obtained in step c).
10. The method according to claim 9, characterized in that Step b) of performing gradient heat treatment on the component obtained in step a) comprises: b1 - first heating a region of the component to a first temperature (T1) that is above the solvus temperature of the γ' phase of the superalloy and below the melting temperature of the superalloy.
11. The method according to any one of claims 9 or 10, characterized in that The final heat treatment step c) comprises the following consecutive steps: c1 - placing the entire component obtained in step b) in a solution, the temperature of which is lower than the solvus temperature (T2) of the γ' phase of the superalloy; c2—cooling or quenching the entire component obtained in step c1); c3—subjecting part or all of the component obtained in step c2) to at least one tempering treatment, advantageously at a temperature in the range of 730°C to 870°C, in order to precipitate M 23 C6 type carbides, where M=Cr, Mo or W.
12. A component made of a superalloy according to any one of claims 1 to 7 or a superalloy powder according to claim 8, said component having a dual microstructure, advantageously obtainable by a method according to any one of claims 9 to 11.
13. The component according to claim 12, characterized in that The component is a turbomachine component, advantageously a turbine component, in particular a turbine disk, a compressor disk, a ring, a flange or a turbine housing.
